EFFECT OF SELECTED MACROECONOMIC VARIABLES ON STOCK MARKET VOLATILITY IN NIGERIA - Hauwa Bayero TIJJANI; Prof Sheikh Ahmad Abdullahi; Dr Ibrahim Mohammed; Dr Isma’il Tijjani Idris (Gusau Journal of Accounting and Finance, 2024)
The Nigerian economy has undergone significant changes in terms of policies that are aimed at improving the performance of the economy and to be able to attract foreign direct investments. It is observed that the performance of the stock market depends to a large extent on the economic condition of the country hence macroeconomic variables are said to have potential effect on stock market volatility. The study focused on macroeconomic variables such as Economic recession, inflation rate, interest rate and stock market liberalisation using monthly data from February 2010 to September 2022. The Augmented Dickey Fuller (ADF) and Philip Perron (PP) unit root tests were conducted on the time series data. The ARCH LM tests was also carried out and the EGARCH model was estimated under the assumption of normally distributed model. The ARCH tests results revealed that there exists ARCH effects in the NGX stock returns implying the presence of volatility clustering in the return series. The results also revealed that Economic recession has a negative impact on stock market volatility. Inflation rate was also found to have a significant positive effect and Interest rate has a positive insignificance effect on volatility. Stock market liberalisation was also found to have a significant negative impact on volatility. The findings also indicate volatility persistence in the Nigerian stock market and that bad news generates higher volatility than good news of the same magnitude. It is recommended that regulators should come up with policies towards restoration of investor’s confidence in the market. Nigerian exchange group should also develop robust risk management strategies to protect investments during economic downturns. This could include diversifying portfolios and using hedging techniques to ensure minimum volatility in stock market prices.